Floristic And Ethnobotanical Studies Of Medicinal Plants Of The City Of El -Jadida (MOROCCO) - Briguiche, Hanae; Zidane, Lahcen (Lazaroa, 2016)
Abstract: BRIGUICHE. H, ZIDANE. L. Floristic And Ethnobotanical Studies Of Medicinal Plants Of The City Of El -Jadida (MOROCCO). In the framework of the ethnobotanical studies on medicinal plants undertaken by the Laboratory of Biodiversity and Natural Resources of the Faculty of Sciences of Kenitra (Morocco), we are interested in the area of El Jadida which presents a rather important floristic richness thanks to changes in its ecological conditions By using 204 questionnaire, the ethnobotanical surveys were conducted in the field during the years 2012-2013. The location of the different sampling sites was determined by the stratified sampling method. The analysis of the results obtained from the questionnaires and forms using statistical processing allowed us to identify 70 plant species distributed in 69 genera and 37 families. These results also show that most of these species are mainly used in the care of the digestive system and respiratory system. The seed is the most used part in local traditional medicines and the decoction is the most frequent mode with a rate of 31%. The species Origanum compactum is the most used by the population of the city of El Jadida 47 quotes.